Factors affecting signal quality in implantable cardiac monitors with long sensing vector. Issue 4 (21st June 2021) - Forleo, Giovanni B.; Amellone, Claudia; Sacchi, Riccardo; Lombardi, Leonida; Lucciola, Maria Teresa; Scotti, Valentina; Viecca, Maurizio; Schiavone, Marco; Giacopelli, Daniele; Giammaria, Massimo
Abstract: Purpose: Electrical artefacts are frequent in implantable cardiac monitors (ICMs). We analyzed the subcutaneous electrogram (sECG) provided by an ICM with a long sensing vector and factors potentially affecting its quality. Methods: Consecutive ICM recipients underwent a follow‐up where demographics, body mass index (BMI), implant location, and surface ECG were collected. The sECG was then analyzed in terms of R‐wave amplitude and P‐wave visibility. Results: A total of 84 patients (43% female, median age 68 [58‐76] years) were enrolled at 3 sites. ICMs were positioned with intermediate inclination (n = 44, 52%), parallel (n = 35, 43%), or perpendicular (n = 5, 6%) to the sternum. The median R‐wave amplitude was 1.10 (0.72‐1.48) mV with P waves readily visible in 69.2% (95% confidence interval, CI: 57.8%‐79.2%), partially visible in 23.1% [95% CI: 14.3%‐34.0%], and never visible in 7.7% [95% CI: 2.9%‐16.0%] of patients. Men had higher R‐wave amplitudes compared to women (1.40 [0.96‐1.80] mV vs 1.00 [0.60‐1.20] mV, P = .001), while obese people tended to have lower values (0.80 [0.62‐1.28] mV vs 1.10 [0.90‐1.50] mV, P = .074). The P‐wave visibility reached 86.2% [95% CI: 68.3%‐96.1%] in patients with high‐voltage P waves (≥0.2 mV) at surface ECG. The sECG quality was not affected by implant site. Conclusion: In ordinary clinical practice, ICMs with long sensing vector provided median R‐wave amplitude above 1 mV and reliable P‐wave visibility of nearly 70%, regardless of the position of the device. Women and obese patients showed lower but still very good signal quality. Abstract : Electrical artefacts are frequent in implantable cardiac monitors (ICMs). We analysed the subcutaneous electrogram (sECG) provided by an ICM with a long sensing vector and factors potentially affecting its quality. In ordinary clinical practice, ICMs with long sensing vector provided median R wave amplitude above 1 mV and reliable P wave visibility of nearly 70%, regardless of the position of the device. Women and obese patients showed lower but still very good signal quality.